Impact of Sedimentation and Navigation Aid Deficiencies on Ship Maneuverability and Grounding Accidents in Maritime Operations - Ahmad Wahid; Larsen Barasa; Marudut Bernadtua Simanjuntak (Greenation Research & Yayasan Global Resarch National, 2026)
Sedimentation and navigation aid deficiencies constitute two interacting technical hazards that persistently contribute to ship grounding accidents, yet their combined effect on vessel maneuverability remains underexamined in qualitative, multi-stakeholder research. This study investigates how sedimentation levels and navigation aid reliability jointly affect ship maneuverability and grounding risk in Indonesian maritime operations. A qualitative design was employed, drawing on semi-structured interviews and focus group discussions with 20 participants: 2 senior maritime professionals with over 20 years of operational experience, 5 maritime vocational lecturers, and 13 recent maritime graduates. Data were analyzed using a systematic six-phase thematic analysis with intercoder verification (Cohen's kappa κ = 0.81). The results reveal significant cross-group score differentials: experts rated chart accuracy at 8.9 and under-keel clearance management at 8.5, while graduates scored rudder effectiveness at 7.2 and stopping distance management at 7.1 — identifying these hydrodynamic parameters as the most critically underprepared domains in current vocational training. The study makes three specific contributions. First, it demonstrates empirically that the education–industry gap in sedimentation risk management is most acute in hydrodynamic competency rather than navigational aid familiarity. Second, it identifies real-time monitoring and predictive sediment modeling as the technological interventions with the broadest stakeholder consensus. Third, it proposes a structured curriculum integration pathway for sedimentation risk management in Indonesian maritime polytechnics.